Academic communities: The role of journals and open-access mega-journals in scholarly communication. Issue 1 (14th January 2019) - Wakeling, Simon; Spezi, Valerie; Fry, Jenny; Creaser, Claire; Pinfield, Stephen; Willett, Peter
Abstract : Purpose: The purpose of this paper is to provide insights into publication practices from the perspective of academics working within four disciplinary communities: biosciences, astronomy/physics, education and history. The paper explores the ways in which these multiple overlapping communities intersect with the journal landscape and the implications for the adoption and use of new players in the scholarly communication system, particularly open-access mega-journals (OAMJs). OAMJs (e.g. PLOS ONE and Scientific Reports ) are large, broad scope, open-access journals that base editorial decisions solely on the technical/scientific soundness of the article. Design/methodology/approach: Focus groups with active researchers in these fields were held in five UK Higher Education Institutions across Great Britain, and were complemented by interviews with pro-vice-chancellors for research at each institution. Findings: A strong finding to emerge from the data is the notion of researchers belonging to multiple overlapping communities, with some inherent tensions in meeting the requirements for these different audiences. Researcher perceptions of evaluation mechanisms were found to play a major role in attitudes towards OAMJs, and interviews with the pro-vice-chancellors for research indicate that there is a difference between researchers' perceptions and the values embedded in institutional frameworks. Originality/value: This is the first purely qualitative study relating to researcher perspectives on OAMJs. The findings of the paper will be of interest to publishers, policy-makers, research managers and academics.